THE ENFLUENCE OF REPRICIPITATION METHODS PARACETAMOL CRYSTAL USING SOLVENT ETHANOL IN FABRICATION PROCESS ON PHYISICAL PROPERTIES OF TABLET - Tri Yulianti; Achmad Fudholi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
Paracetamol is the most material drug used in Indonesia. But it’s difficull in processing of the tablet because of capping tendency. The effect of paracetamol reprecipitation by using etanol solven during fabrication process to physical characteristic of tablets of has been studied, and to know the effect of paracetamol. In this studies made five formulas : paracetamol was sprayed by etanol, paracetamol was added filler then sprayed by etanol, paracetamol was added disintegrant then sprayed by elanol, granulating the paracetamol then was sprayed by etanol and paracetamol was without sprayed by etanol. Results showed that granules had been sprayed by etanol before the granulation have characteristic of flow materials was better, the friability of the granules decreased and compressibility of the granules was better. Hardness of tablets relatively increased, the friability of the tablets relative decreased and the disintegration time of tabltets increased. Generally, reprecipitation of paracetamol during the fabrication process, the physical properties of granuls and tablet were better.Key words : paracetamol, reprecipitation, physical properties of tablets